Effect of Ti addition holding time on casting quality and mechanical properties of A356 alloy - Gurtaran, Mikdat; Uludağ, Muhammet (Springer International Publishing Ag, 2020)
Bifilms are casting defects that occur due to the incorporation of surface oxide film into the melt. Thus, they act as a crack in the liquid. Once they remain in the structure, they decrease mechanical properties owing to their negative effect on porosity formation. One of the most fundamental problems to be avoided in this frame is the reduction of the bifilms or the cleaning of the liquid metal to prevent the porosity formation. In this study, A356 (Al-7Si-0.3 Mg) alloy was used. AlTi5B1 master alloy was added as a grain refiner. The effect of Ti on casting quality and mechanical properties changes by holding time was evaluated. The results were examined statistically by Weibull analysis. It was found that the presence of bifilms can be reduced as holding time increases after adding Ti. The tensile properties were increased as the holding time increased. Additionally, the optimum holding time may be 40 min after Ti addition for high casting quality and good mechanical properties.
Keywords: A356 alloy; Grain refinement; Holding time; Mechanical properties; Casting quality